ANALISIS KETERSEDIAN BAHAN AJAR PADA MATA PELAJARAN IPA DI KELAS IV SD N 1 CEMPAGA - Ani, Ni Wayan Epi (Universitas Muhammadiyah Mataram, 2024)
This research aims to determine the availability of teaching materials for science subjects in class IV. The type of research is a qualitative descriptive approach. The research subject was a fourth grade teacher at SD Negeri 1 Cempaga and analyzed the availability of science teaching materials as the research object. The instruments used were interviews and observations. Next, the data was analyzed descriptively qualitatively. The research results show that teachers use printed teaching materials and the media used are concrete media and digital media. Teachers in class IV at SD Negeri 1 Cempaga need more varied teaching materials so that they can support the science learning process.